2023
DOI: 10.1007/s11332-023-01059-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a nutrition program for weight loss during the pre-competition period on the body composition, hydration, and mood profile of elite Greco–Roman wrestlers

Abstract: Objective The study aimed to investigate the effect of a nutrition program introduced among elite Greco-Roman wrestlers during weight loss period prior to the competition on the athletes' body composition, hydration, and mood. Methods The experimental group comprised from the Greco-Roman Wrestling National Team (U23) of different weights (n = 8) and the control group consisted of substitute athletes (n = 8) with the same weights with the experimental group. To achieve the target weight, the experimental group … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Analyses show that adolescent combat sports athletes are sometimes dehydrated as early as 30 days before competition [48]. In a study conducted during a 3-week wrestling camp, it was shown that diet and individual adjustment of fluid supply influence the results achieved during competition and also improve the athlete's mood [49]. The effect of hydration and diet during the camp on post-exercise recovery was also demonstrated by the results obtained in the authors' study.…”
Section: Discussionmentioning
confidence: 60%
“…Analyses show that adolescent combat sports athletes are sometimes dehydrated as early as 30 days before competition [48]. In a study conducted during a 3-week wrestling camp, it was shown that diet and individual adjustment of fluid supply influence the results achieved during competition and also improve the athlete's mood [49]. The effect of hydration and diet during the camp on post-exercise recovery was also demonstrated by the results obtained in the authors' study.…”
Section: Discussionmentioning
confidence: 60%